Comparable analysis of information and communication technologies in Lithuania and Finland - Bazaras, Darius; Ledauskaitė, Kristina; Palšaitis, Ramūnas (Transport, 2010)
Information exchange and making business transactions via the Internet and E-mail are very common nowadays. Thus, it is very important to investigate the use of applied Information and Communication Technologies (ICT) in activities undertaken by business and transport companies examining the levels the companies are making investments and to assess needs for a wider use of ICT in the logistics and transport companies. A number of authors in the Baltic States are analyzing ICT in separate business areas, for example transportation, warehousing, marketing, management etc. but none of those analyzes the use and development of ICT inside the company. The article describes the situation of using and developing ICT in the Baltic Sea Region and makes a comparison of Lithuanian and Finnish companies. Finland was chosen for benchmarking because research on ICT in the Baltic Sea Region (BSR) showed that the situation of using ICT in Lithuania and its neighborhood countries was similar.First published online: 24 Jun 2011